Bile Duct Injury During Cholecystectomy: Necessity to Learn How to Do and Interpret Intraoperative Cholangiography - Christou, Niki; Roux-David, Alexia; Naumann, David N.; Bouvier, Stephane; Rivaille, Thibaud; Derbal, Sophiane; Taibi, Abdelkader; Fabre, Anne; Fredon, Fabien; Durand-Fontanier, Sylvaine; Valleix, Denis; Mathonnet, Muriel (Frontiers in Medicine, 2021)
Introduction: Biliary duct injury (BDI) is a serious complication during cholecystectomy. Perioperative cholangiography (POC) has recently been generating interest in order to prevent BDI. However, the current literature (including randomized controlled trials) cannot conclude whether POC is protective or not against the risk of BDI. The aim of our study was to investigate whether POC could demonstrate earlier BDI and which criteria are required to make that diagnosis. Methods: We performed a retrospective study between 2005 and 2018 in our French tertiary referral center, which included all patients who had presented following BDI during cholecystectomy. Results: Twenty-two patients were included. Nine patients had POC, whereas 13 did not. When executed, POC was interpreted as normal for three patients and abnormal for six. In this latter group, only two cases had a BDI diagnosed intraoperatively. In other cases, the interpretation was not adequate. Conclusion: BDIs are rare but may reduce patients' quality of life. Our study highlights the surgeon's responsibility to learn how to perform and interpret POC in order to diagnose and manage BDIs and potentially avoid catastrophic consequences.